STUDY OF CHILDREN'S LITERATURE AS TEACHING MATERIAL FOR ELEMENTARY SCHOOLS IN LEARNING MORAL CHARACTER OF STUDENTS - Azmi Alwi, Nur; Agasi, Diren; Surya Perdana, Andika; Sya’idah, Nadia (RADJA PUBLIKA, 2022)
Problems regarding character and morals that occur in elementary school students are a hot topic of discussion. The character and moral crisis that is happening to the Indonesian nation today is extraordinary. In recent years, we are often presented with information about how corrupt and depraved the morals of students are. Starting with cases of sexual harassment that occur in children which makes us very sad. The fact that has happened is the shared responsibility of all groups, be it the family, teachers, government, and the social environment where the child is. Thus, children's literature becomes a solution to make improvements to the character and morals of students. Children's literature must be re-presented and intended to the maximum for students. The purpose of this research is to describe how the study of character and moral teaching in the Story of a Fairy Tale and to provide input for children's literature is used as teaching material that is entertaining and fun for students.